Constructions of Space: Exploring Photographic Images in Forest School - Garden, Ange (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
This research builds on the recently published paper (Garden, 2022c), which explored through interviews the use of iPads as cameras to enhance Forest School practice. Children’s perspectives of the Forest School space captured what was important to them on camera (Garden, 2022c). Working with the same group of 32 Key Stage 2 children selected from two UK primary schools, the research explored the images captured on iPad cameras during the follow-on session. The unstructured interviews explored the children’s feelings and meanings associated with the images captured in the Forest School space using Interpretive Phenomenological Analysis (IPA). The photographs can be understood within the themes of ‘play with technology’, ‘soft fascination’ and ‘place attachment’, all of which are inherent in the Forest School ethos. Suggestions for future research include reflections on the ways the capturing of images of Forest School can encourage peer collaboration whilst considering the relative influence of space.